Beneficial effects of replacing diet beverages with water on type 2 diabetic obese women following a hypo-energetic diet: a randomized, 24-week clinical trial - Madjd, Ameneh; Taylor, Moira A.; Delavari, Alireza; Malekzadeh, Reza; MacDonald, Ian A.; Farshchi, Hamid R. (Wiley, 2016)
Abstract AIMS: To compare the effect of replacing diet beverages (DBs) with water or continuing to drink DBs in patients with type 2 diabetes during a 24-week weight loss program. The primary endpoint was the effect of intervention on weight over a 24-week period. The main secondary endpoints included anthropometric measurement and glucose and fat metabolism during the 24-week period. METHODS: A total of 81 overweight and obese women with type 2 diabetes, who usually consumed DBs in their diet, were asked to either substitute water for DBs or continue drinking DBs five times per week after lunch for 24 weeks (DBs group) during a weight loss program. RESULTS: Compared with the DBs group, the water group had a greater decrease in weight (water, -6.40 ± 2.42 kg; DBs, -5.25 ± 1.60 kg; P = .006), in BMI (water, -2.49 ± 0.92 kg/m2 ; DBs, -2.06 ± 0.62 kg/m2 ; P = .006), in FPG (water, -1.63 ± 0.54 mmol/L; DBs, -1.29 ± 0.48 mmol/L, P = .005), in fasting insulin (water, -5.71 ± 2.30 m lU/mL; DBs, -4.16 ± 1.74 m lU/mL, P = .011), in HOMA IR (water, -3.20 ± 1.17; DBs, -2.48 ± 0.99, P = 003) and in 2 hour postprandial glucose (water, -1.67 ± 0.62 mmol/L; DBs, -1.35 ± 0.39 mmol/L; P = 0.027) over the 24-week period. However, there was no significant time × group interaction for waist circumference, lipid profiles and HbA1c within both groups over the 24-week period. CONCLUSION: Replacement of DBs with water after the main meal in obese adult women with type 2 diabetes may lead to more weight reduction during a weight loss program.